Rozmowa z Jerzym Hoffmanem - Krupnyk, Liubov (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
An interview with the Polish film director Jerzy Hoffman was recorded on 11–12 July 2022 at his estate in the village of Sikory Yuskie in the Warmian-Masurian Voivodeship. Jerzy Hoffman is perhaps the most popular Polish film director in Ukraine. His films gained recognition even before Ukraine gained independence. However, his most notable work is Ogniem i mieczem [With Fire and Sword, 1999], which starred the great Ukrainian actor Bohdan Stupka (1941–2012) as Hetman Bohdan Chmielnicki. The collaboration continued in the film The Old Tale. When the Sun Was a God (2003). In 2008 Jerzy Hoffman made a four-part documentary film Ukraine. The Birth of a Nation. The conversation touched on issues related to these films, completed and unrealized projects on Ukraine, reflections on the history of Polish-Ukrainian relations and the role of Jerzy Hoffmann’s work in establishing them. As a filmmaker who closely follows events in Ukraine, he shared his impressions and predictions about how the ongoing war will change and transform Ukraine and the world.